Seasonality of Hematological Indicators of Fish Blood - X. T., Yuldoshev (American Journal of Biology and Natural Sciences, 2025)
This article presents a comparative analysis of biomorphological parameters of fish cultivated in various ecological regions of Uzbekistan. The studied indicators include standard body length (cm), total weight (g), eviscerated weight (g), individual absolute fecundity (thousands of eggs), and individual relative fecundity (eggs/g). The research was conducted across different months and districts. The results provide insights into how ecological factors influence the fecundity and biometric development of fish.